Pengaruh Model Pembelajaran Kooperatif Tipe Think-Talk-Write (TTW) Terhadap Partisipasi Siswa dan Hasil Belajar Siswa dalam Pelajaran Matematika - Muh. Ikhsan Ibrahim; Awi; Muh. Dinar (Issues in Mathematics Education (IMED), 2017)
This study aims (1) To know the score of student participation taught by cooperative learning model Think-Talk-Write (TTW); (2) To know the value of mathematics learning outcomes which taught by cooperative learning model of Think-Talk-Write (TTW); (3) To know the influence of cooperative learning model Think-Talk-Write (TTW) toward student participation; (4) To know the influence of cooperative learning model Think-Talk-Write (TTW) toward student's mathematics learning outcomes.Research instrument used in the form of learning activity sheet, student activity observation sheet, student participation questionnaire in learning process and test of mathematics learning result. The data collected by the instrument is analyzed using descriptive and inferential statistical techniques. The results showed that (1) The participation of class studentsscore of 35,05; (2) Mathematics learning result of students in high category with average 83,50; (3) There is influence the use cooperative learning model TTW toward student participation; (4) There is influence the use cooperative learning model TTW toward mathematics learning outcomes. It can be concluded that there is influence of cooperative learning model TTW toward student participation and student mathematics learning outcomes.